Misunderstandings - Weizsäcker, Georg (Open Book Publishers, 2023)
What do we expect when we say something to someone, and what do they expect when they hear it? When is a conversation successful? The book considers a wide set of two-person conversations, and a bit of game theory, to show how conversational statements and their interpretations are governed by beliefs. Thinking about beliefs is suitable for communication analysis because beliefs are well-defined and measurable, allowing to differentiate between successful understandings and their less successful counterparts: misunderstandings.